GASTROINTESTINAL PARASITES OF BALI CATTLE MAINTAINED AT THE FINAL LANDFILLS IN SUWUNG DENPASAR - Dwinata, Made; Suratma, Nyoman Adi; Oka, Ida Bagus Made; Agustina, Kadek Karang (Buletin Veteriner Udayana; Vol. 10 No. 2 Agustus 2018DO - 10.24843/bulvet.2018.v10.i02.p09, 2018)
Infectious parasitic diseases gastrointestinal parasites in cattle can cause high economic losses due to parasites and livestock compete for mutual fighting nutrients, damage to internal organs, decreasing productivity and mortality in cattle. This study aimed to determine the prevalence and identifying the digestive tract parasites of bali cattle reared in the final landfills Suwung, Denpasar. The number of samples was examined as many as 100 cattle feces were examined using sedimentation and floatation methods. The result showed that the prevalence of digestive tract parasitic infection in bali cattle were maintained at the final landfills in Suwung Denpasar by 65%. Types of infecting parasites were strongyl type 50% , Trichuris sp. 11% , Strongyloides papilosus 4% , Toxocara Vitolorum 3% , Fasciola gigantika 5%, Paramphistomum sp. 11% and Eimeria sp. 7%.